Mulheres em revista: uma sociologia da compreensão do feminino no Brasil presbiteriano (1994-2002) - Campos, Breno Martins (2006)
Women in review: a sociology of knowledge of the feminine in the Presbyterian Brazil (1994-2002) is a thesis with three sociological interests: knowledge, domination and religion. With its focus on the Presbyterian Church of Brazil, it searches to understand the reason why women are excluded from the positions legally stated of power and domination: the ordered office. Its historical cut is the transition from the 20th to 21st century, in which there were official attempts and an alto for alteration of denominational status quo. Two enterprises of constitutional reformation were proposed and debated in the competent councils in less than eight years, that included in the discussion the alteration of women statute in Presbyterian Church of Brazil, for her official space of actuation was amplified and her condition as a member equaled to the men s, with complete rights. The same historical period watched to a movement in which the puritan ethics and fundamentalist theology were used by the reactionary group to reaffirm the tradition and stop the opening of a new time, more feminine, dialogic and inclusive. Inheritance of the United States protestant missions of the 19th century for Brazilian churches, the puritan ethics proposes as a way of salvation a kind of active ascetic practices that deny the world at the same time in which fight for its transformation; the fundamentalism is the literalist Bible interpretation pattern that works for the arrest of the truth rather than to exclude dissent groups and people. The hermeneutical literalism forbids that biblical texts could be used in behalf of feminine ordering; the puritan ethics suggests or imposes to the women a proper space under to men, at home and in the church. The changing projects intended by the Presbyterian Church of Brazil high hierarchy, leaded by Rev. Guilhermino Cunha, were aborted, in dynamic peculiar to the function of religious field. In the very 21st century women cannot be pastors, elders or deacons in IPB: condition in such a flagrant contradiction with the democratic-representative system of government. The reading of official speeches of the denomination, by its journal, the Brasil Presbiteriano, and by Sociedade Auxiliadora Feminina s magazine, the SAF em Revista, allows to affirm that the Brazilian Presbyterian leaderships, masculine and feminine, at the doors of 21st century, opted for the permanence in the 20th century, or rather than, in 19th century. To open the 21st century, or to open itself to it, is the challenge for the contemporary Presbyterian Church of Brazil, specially to the women, in order that the religious institution promotes and amplifies the internal dialogue, inter-religious and with society, the first steps to the legitimate exercise of democracy, inclusion, fight against prejudice and discrimination, and for the establishment of an ethical project for all